Search for Kaluza-Klein graviton emission in pp̄ collisions at √s = 1.8 TeV using the missing energy signature - Acosta, D; Affolder, T; Akimoto, H; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2004)
The results of a search for the direct production of Kaluza-Klein (KK) graviton modes using the rate of events with one or two energetic jets and large ET at the Collider Detector at Fermilab (CFD) were reported. The search was based on 84±4 pb-1 of integrated luminosity recorded with the CDF detector. The final state of large missing transverse energy and one or two high energy jets was also investigated. The calculation of graviton emission was based on the effective low-energy theory that was valid below the scale MD.